The utility of chest ultrasound-guided fine-needle biopsy in the diagnosis of plasmacytoma - S S Benbarka; P T Shubert; E M Irusen; B W Allwood; C F N Koegelenberg (African Journal of Thoracic and Critical Care Medicine, 2022)
Background. Plasmacytoma is a plasma cell dyscrasia originating from a single clone of plasma cells of B-lymphocyte lineage and produces a monoclonal immunoglobulin. Transthoracic fine-needle aspiration (TTNA) under ultrasound (US) guidance is a well-validated technique for the diagnosis of many neoplasms and has been shown to be safe and cost effective, with diagnostic yields comparable to more invasive techniques. However, the role of TTNA in the diagnosis of thoracic plasmacytoma is not well established.